Makna Tanah Leluhur Bagi Naomi Berdasarkan Teks Rut 1:1-22 - Nelci Nafalia Ndolu; Marsi Bombongan Rantesalu (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2019)
The Meaning of Ancestral Land For Naomi Based on Ruth 1: 1-22. The story of Naomi in Ruth 1: 1-22 is closely related to her ancestral land in Bethlehem-Judah. In Ruth 1: 1-3, Naomi is told to make a choice to leave her ancestral land. But Ruth 1: 6 explains that Naomi finally chose to return to her ancestral lands in Bethlehem-Judah after experiencing various suffering and tragedies in the land of Moab. Naomi's choice implied Naomi's perception of the economic, cultural, political and religious meaning of her ancestral land. Based on Ruth 1: 6-19-22, Naomi continues to acknowledge her ancestral land as the